Standardization of catch per unite effort for chub mackerel Scomber japonicus in the waters at Kuril Islands - E. P. Chernienko; I. S. Chernienko (Известия ТИНРО)
Chub mackerel became an important object of Russian fishery in the NorthWest Pacific since 2015. Annual catch of the species by Russian fleet reached 87,388 t in 2021. The data of trawl catches by Russian fishing vessels in the national waters in autumn of 2015–2021 are considered for possibility of CPUE standardization taking into account the factors of fishing gear and environments. Generalized additive models (GAM) were used as the method, the best model was chosen using the information criteria of Akaike and Schwarz. The selected model explains 63% of dispersion and includes such predictors as coordinates of catch, date of catch, vessel length, engine power, number of fishing vessels, and SST. Influence of these factors on CPUE is interpreted and discussed.